Feeding frequency affect feed utilization of tilapia under biofloc system condition during nursery phase - Rania S. Mabroke; Abd El-Naem F.A Zidan; Al-Azab Tahoun; Hesham R.A. Mola; Hanan Abo- State; Ashraf Suloma (Aquaculture Reports, 2021)
Feed frequency is one of the factors that have great effect on feed utilization. This factor was previously examined under clear water condition but not under biofloc condition. Different feed frequencies (FF); one (FF1), two (FF2), three (FF3), four (FF4) and five (FF5) times a day were evaluated under biofloc system condition. Fish with initial body weight of 7.9 g ± 0.03 were stocked (20 fish tank−1) in fifteen tanks (55 L). Total ammonia, nitrite, nitrate, and pH values were within acceptable limits for Nile tilapia. No significant differences were recorded among different feeding frequency treatments regarding growth performance parameters. FF2 and FF5 groups had the best significant values for feed conversion and protein efficiency ratios. Ash content of the collected biofloc slightly differed(P ≤ 0.05) among treatments. The highest zooplankton count was recorded for FF5 treatment while, the lowest was recorded for FF2 treatment. Rotifers was the most dominant group (70–92 %) and the highest percentage were recorded for FF2 (92.4 %). FF5 showed a unique development in zooplankton community where, nematodes only appeared in this treatment. From economical prospective, feeding tilapia juveniles twice daily under biofloc condition will save labor costs or feeder energy and improve feed utilization than other frequencies.